Enhanced photonic spin Hall effect with subwavelength topological edge states. Issue 4 (9th May 2016) - Slobozhanyuk, Alexey P.; Poddubny, Alexander N.; Sinev, Ivan S.; Samusev, Anton K.; Yu, Ye Feng; Kuznetsov, Arseniy I.; Miroshnichenko, Andrey E.; Kivshar, Yuri S.
Abstract : Two seemingly different subjects, namely topological photonics and optical spin Hall effect, are bridged together by predicting theoretically and demonstrating experimentally the topology‐enhanced photonic spin Hall effect. By employing near‐field scanning techniques, the selective excitation of the edge states controlled by the handedness of an incident wave is mapped directly, for both optical and microwave experiments. The specific features of the photonic structure symmetry required to enhance the photonic spin Hall effect through topological properties are revealed. Abstract: Photonic structures offer unique opportunities for controlling light‐matter interaction, including the photonic spin Hall effect associated with the transverse spin‐dependent displacement of a light beam that propagates in specially designed optical media. However, due to small spin‐orbit coupling, the photonic spin Hall effect is usually weak at the nanoscale. Here we suggest theoretically and demonstrate experimentally, in both optics and microwave experiments, the photonic spin Hall effect enhanced by topologically protected edge states in subwavelength arrays of resonant dielectric particles. Based on direct near‐field measurements, we observe the selective excitation of the topological edge states controlled by the handedness of the incident light. Additionally, we reveal the main requirements to the symmetry of photonic structures to achieve the topology‐enhanced spin Hall effect, and also analyse the robustness of the photonic edge states against the long‐range coupling.